STRATEGI FUNDRAISING, MANAJEMEN PENGELOLAAN, DAN PENYALURAN DANA ZAKAT, INFAQ, DAN SHADAQAH PADA PANTI YAUMA MAJALENGKA - Ayu Gumilang Lestari; Neng Dewi Idawati (Program Studi Akuntansi Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2022)
Sharia economics plays an important role in tackling poverty, including Zakat, Infaq and Shodaqoh which are potential sources of funds that can be utilized to realize people's welfare. In realizing the welfare of the people, Zakat, Infaq and Shodaqoh need an intermediary, namely an institution or foundation that manages and distributes Zakat, Infaq and Shodaqoh funds. A good Zakat, Infaq and Shodaqoh institution cannot be separated from the fundraising strategy, management management and distribution of trustworthy funds. The purpose of this study was to find out how the fundraising was carried out by the Yauma Majalengka Panti, how the management of Zakat, Infaq and Shodaqoh funds was carried out by the Yauma Majalengka Panti and how the distribution of Zakat, Infaq and Shodaqoh funds was carried out by the Yauma Majalengka Panti. This type of research is a field and library research using a descriptive qualitative approach. Data collection techniques in this study are: interviews, observation and documentation. Data sources consist of secondary data and primary data. by conducting interviews with several employees of Panti Yauma Majalengka and observing from existing data and from supporting data. The results of the research study on the fundraising, management and distribution of Zakat Infaq and Shodaqoh funds at the Yauma Majalengka Orphanage have been carried out according to the planned program, namely the fundraising strategy using direct and indirect methods. The direct method is by: picking up care, charity boxes, pamphlets, close friends, online applications and social media, while fundarising indirectly through religious activities and seminars. The management of Zakat Infaq and Shodaqoh funds is carried out properly, the management system uses the PSAK 109 system, the distribution of Zakat Infaq and Shodaqoh funds is in accordance with fiqh, namely distributed to 8 groups (asnaf) in its distribution also has a program in each month, namely compensation for orphans and poor people, basic necessities, care for the elderly, scholarships and care for the Qur’an teacher.